Use the zeroes to figure this out... x=-18, y=9
Answer:
Step-by-step explanation:
I think you have the question incomplete, and that this is the complete question
sin^4a + cos^4a = 1 - 2sin^2a.cos^2a
To do this, we can start my mirroring the equation.
x² + y² = (x + y)² - 2xy,
This helps us break down the power from 4 to 2, so that we have
(sin²a)² + (cos²a)² = (sin²a + cos²a) ² - 2(sin²a) (cos²a)
Recall from identity that
Sin²Φ + cos²Φ = 1, so therefore
(sin²a)² + (cos²a)² = 1² - 2(sin²a) (cos²a)
On expanding the power and the brackets, we find that we have the equation proved.
sin^4a + cos^4a = 1 - 2sin^2a.cos^2a
Answer:
a is 3,2 b is 1,-2 and c is -2,1
Step-by-step explanation:
u take the first number then you just put em together
Answer: 3
Step-by-step explanation:
The degree of a polynomial is the biggest exponent in the expression
![5x^{3} +3x^{2} -4x + 1](https://tex.z-dn.net/?f=5x%5E%7B3%7D%20%2B3x%5E%7B2%7D%20-4x%20%2B%201)
yep, basically 3
Option 1.
and option 4.
are equivalent to ![-2(5x-\frac{3}{4} ).](https://tex.z-dn.net/?f=-2%285x-%5Cfrac%7B3%7D%7B4%7D%20%29.)
Step-by-step explanation:
Step 1:
The given expression is expanded as follows.
The -2 is multiplied with the 5x and then the -2 is multiplied with the
.
So the expression becomes as follows;
![-2(5x-\frac{3}{4} ) = (-2)(5x) + (-2)(-\frac{3}{4}).](https://tex.z-dn.net/?f=-2%285x-%5Cfrac%7B3%7D%7B4%7D%20%29%20%3D%20%28-2%29%285x%29%20%2B%20%28-2%29%28-%5Cfrac%7B3%7D%7B4%7D%29.)
This is the first option given so the first expression is equivalent.
Step 2:
![-2(5x-\frac{3}{4} ) = (-2)(5x) + (-2)(-\frac{3}{4}) = -10x + \frac{6}{4} = -10x + \frac{3}{2} .](https://tex.z-dn.net/?f=-2%285x-%5Cfrac%7B3%7D%7B4%7D%20%29%20%3D%20%28-2%29%285x%29%20%2B%20%28-2%29%28-%5Cfrac%7B3%7D%7B4%7D%29%20%3D%20-10x%20%2B%20%5Cfrac%7B6%7D%7B4%7D%20%3D%20-10x%20%2B%20%5Cfrac%7B3%7D%7B2%7D%20.)
Of the other four options, only the fourth expression has the fraction
so the fourth expression is also equivalent.
Expressions 1 and 4 are equivalent to the given expression.